Global DNA hypomethylation in canine mammary tumors - Decuadro, Alicia; Montenegro, María del Carmen; Llambí , Silvia; Balemian, Nariné; Cappetta, Mónica (Revista Científica de la Facultad de Ciencias Veterinarias, 2025)
Due to its influence in transcriptional potential of genes, genetic regulation by means of epigenetic mechanisms is essential for normal growth and development. In mammary cancer, epigenetic modifications play a key role for its development and progression. In early carcinogenesis stages, due to genetic alterations or environmental factors, chromatin structure alterations due to DNA methylation and post-translational modifications of DNA-bound proteins may appear. As with other types of tumor, genome-wide hypomethylation and hypermethylation of specific genes, particularly in CpG islands that normally are not methylated, are observed. In order to compare global DNA methylation levels between tumor tissue and normal mammary tissue, we studied 11 intact female dogs with mammary tumors. Both types of tissue were collected during surgery, with subsequent clinical staging and histopathological classification of tumors. For each animal, DNA was extracted from paired samples of tumor tissue and normal mammary tissue. Global genomic methylation levels were calculated by relative quantitation of 5-methyl-2’-deoxycytidine (5mdC) with HPLC. Results showed that tumoral tissue had a global DNA hypomethylation when compared with normal mammary tissue (P < 0.05). This difference was greater in high histopathological grade tumors, characterized by their aggressive clinical behavior and high metastatic rate. These findings underscore the importance of additional studies in this line of research, with greater sample sizes. In the future, global DNA methylation may be used as a prognosis biomarker for mammary cancer in dogs.